PERANCANGAN KODE KOREKSI KESALAHAN REED SOLOMON CODE RS(31,27) DENGAN MENGGUNAKAN BAHASA VHDL - Mahmudi, Ali; Jasmani, Jasmani (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
Error correction technology is widely applied in the era of data / information exchange today.This technology is widely used to reduce the error rate on the exchange of data / information toacceptable limits. Hamming Code, Reed Muller Code, Golay Code, BCH Code and Reed SolomonCode are some examples of error correction technology that is widely used. This paper presents theReed Solomon Code. Here, the Reed Solomon Code is decoded using the Welch Berlekampalgorithm. The Reed Solomon RS code (31, 27) is designed and designed using the VHDLlanguage, and then simulated using the Altera ModelSim application. The simulation results showthat the RS code (31, 27) goes as expected and is able to correct up to 2 errors.Keywords: Reed Solomon Code, Error Correction, RS code, Welch Berlekamp Algorithm.Â